The need for a mandatory ethical and legal framework for artificial intelligence and algorithms in Colombia - Ulrich Astaiza, William Eugene (DIXI, 2023)
The advance of technology with respect to artificial intelligence (ai) has led academia to question not only how far it can go, but also what are the possible harmful effects it can bring to humanity, which is why, in the absence of legal regulation of the matter, the Presidency of the Republic published the “Ethical framework for artificial intelligence in Colombia” in response to the global dynamics of ai.Objective: To establish the need for the implementation of a mandatory ethical and legal framework for ai and algorithms in Colombia.Methodology: An analysis of the different international cases in which ethical and legal problems of ai and algorithms have been discussed is carried out, and the need for changes at the legislative level for Colombia is proposed.Results: A necessary mechanism for regulation is to turn to the Congress of the Republic to legislate on the ethical and liability aspects of ai and algorithms.Conclusions: The importance and the need to regulate aspects such as ethics and liability of AI and algorithms should encourage Congress to regulate the matter. Likewise, in the hands of the high judicial corporations of Colombia lies the responsibility to create rules that allow the understanding and management of the conflicts raised by ai and algorithms.
Keywords: ethics; artificial intelligence; regulation; liability; algorithms